Magnetic Resonance Venography Findings In A Group Of Patients With Multiple Sclerosis - Al-Baghdady, Ali Qasim (AL-Kindy College Medical Journal, 2019)
Background: Multiple sclerosis is a chronic heterogeneous demyelinating axonal and inflammatory disease involving the Central Nervous System [CNS] white matter with a possibility of gray matter involvement in which the insulating covers of nerve cells in the brain and spinal cord are damaged. This damage disrupts the ability of parts of the nervous system to communicate, resulting in a wide range of signs and symptoms. Cerebral venous insufficiency theory was raised as a possible etiology for the disease at 2008 by Zamboni an Italian cardiothoracic surgeon. This theory was defeated by Multiple Sclerosis[ MS] researchers and scientists who thought that the disease is an autoimmune rather than vascular.Objective: To assess the findings of Magnetic Resonance Venography [MRV] in a group of patients with MS and to compare these results with a healthy control group Magnetic Resonance Venography[ MRV] findings.Type of the study: A case – control cross sectional study.Methods: it was conducted at Neurosciences Hospital MS clinic from Oct.2014 to Dec. 2015, recruiting sequentially 50 patients who attend the MS clinic; 19 male and 31 females, their age was ranged from 16 to 53 year old. Diagnosis of MS was based on fulfillment of McDonald 2010 criteria for MS diagnosis, detailed history , examination and Expanded Disability Status Scale( EDSS)[see Appendix1] were recorded according to structured questionnaire forum. Each patient was send for Magnetic Resonance Venography[ MRV] using 3 Tessla Phillips model Achieva, 2012. The results of MRV were interpreted by specialist radiologist. Statistical analyses were done using SPSS version 21 with P value less than 0.05 was considered significant.Results: Fifty patients with Multiple Sclerosis were involved in the study female 31, male 19, their ages were ranged between 21 and 60 year old. Magnetic Resonance Venography [MRV] findings suggest of venous thrombosis were seen in [4 / 50] 8% of patients and [46 /50] 92% of the patients in this study have no findings of venous thrombosis. The comparison with the control group showed no significant statistical difference.Conclusion: Magnetic Resonance Venography[MRV] finding is not statistically different between healthy people and Multiple Sclerosis patient